Perspective Chapter: A New Bivariate Inverted Nakagami Distribution – Properties and Applications - Aliyu, Ismail Ishaq; Usman, Abubakar; Suleiman, Ahmad Abubakar; Othman, Mahmod; Hanita, Daud; Sokkalingam, Rajalingam; Panitanarak, Uthumporn; Muhammad Azrin, Ahmad (IntechOpen, 2023)
In this work, a new bivariate inverted Nakagami distribution that can be used to model real-world datasets has been investigated. The newly developed bivariate distribution’s cumulative distribution function and probability density function are defined. The bivariate distribution derives from the Farlie Gumbel Morgenstern, and the marginal density functions are also determined. Some fundamental estimation techniques, such as maximum-likelihood estimation and inference functions for margins, are used to derive the parameters of its estimates. Applications to real-world datasets pertaining to kidney infection diseases and the UEFA Champions’ League group stage for the seasons 2004–2005 and 2005–2006 help to assess the efficacy of the proposed distribution.